A Rare Case of a Gastro-Peritoneal Fistula Following Laparoscopic Sleeve Gastrectomy Successfully Treated with Endoscopic Stenting - Kosai NR,; Khan A,; Mustafa MT,; Zalizawati ZA,; Mohd Firdaus CA,; Leong, JH (Penerbit UKM, 2015)
Gastro-peritoneal fistula is a rare but serious complication of laparoscopic sleeve gastrectomy with significant morbidity and mortality. We present the case of a 42-year-old man who underwent laparoscopic sleeve gastrectomy for morbid obesity and presented later with a history of chronic epigastric pain and severe reflux. Upper gastrointestinal series showed the presence of a communicating fistula between the stomach and the left hemi-diaphragm and peri-splenic area.